CLINICAL CHARACTERISTICS OF COVID-19 AND THE EFFICACY OF VACCINATION IN PATIENTS WITH HEMATOLOGIC MALIGNANCIES - Markovic, Olivera; Divac, Anica; Bukurecki, Ilija; Brankovic, Marija; Jovanovic, Igor; Đuran, Predrag; Zdravkovic, Marija (Srpski medicinski časopis Lekarske komore, 2022)
Patients with hematologic malignancies are at increased risk of severe forms of COVID-19 and have higher mortality, compared to patients with COVID-19 in the general population. The reasons for this include immunosuppression caused by the underlying hematologic disease and/or anticancer therapy received by these patients, advanced age, but also low levels of seroconversion after vaccination. These patients are also at a higher risk of getting infected because of frequent visits to health care facilities and high exposure to other patients. Results from published studies highlight the importance of prevention strategies in these patients, based on infection control measures and physical distancing, but also on well-timed vaccination. Risk factors which have proven to be crucial for severe forms of COVID-19 are age, the presence of comorbidities, malignancy type, progressive disease, and the type of oncologic therapy that these patients receive. Therefore, patients with hematologic malignancies represent a priority group for vaccination, which is recommended by all international professional associations. Considering that these patients are at risk of not developing an adequate immune response to the vaccine, the issues of determining the optimal time period for receiving the vaccine, the optimal dose, and the capacity of developing an immune response to the vaccine in specific groups of patients with hematologic malignancies, are questions that remain unresolved. Studies have shown that, despite the weak immune response to the vaccine, the mortality of vaccinated patients with hematologic malignancies is significantly lower than the mortality of unvaccinated patients. This article provides a review of relevant studies which analyze the characteristics, morbidity and mortality of patients with hematologic malignancies and COVID-19 and the role of vaccination in these patients.